Autologous Stem Cell Transplantation in Multiple Myeloma with Renal Failure: Friend or Foe? - Hongfei Zhong; Xiaojie Xie; Gaosi Xu (Hindawi Limited, 2019)
Autologous stem cell transplantation (ASCT) is a standard treatment for multiple myeloma (MM), but the clinical response and renal curative effect in MM patients with renal failure (RF) remain controversial. The myeloma kidney disease has different types, and most are due to the direct toxic effects of light chain. Although ASCT can effectively clear the light chain, the data of renal function improvement are still limited. We reviewed the published literatures, focusing on the prospective studies, the retrospective analysis studies, and the case reports. RF patients who received ASCT displayed a low survival rate (OS: HR 1.95, 95% CI 1.020 to 3.720; I2=64.9%, P=0.014) and a shorter EFS/PFS (EFS/PFS: HR 1.53, 95% CI 1.090 to 2.140; I2=0%, P=0.669). However, ASCT was feasible and could have the similar clinical response outcomes compared with the normal renal function (CR: OR 1.013, 95% CI 0.569 to 1.804; I2=48.5%, P=0.101; PR: OR 1.013, 95% CI 0.342 to 1.226; I2=46.3%, P=0.144). Moreover, MM with RF after ASCT had a good improvement of renal function and melphalan is still an important factor affecting the treatment of ASCT.